Experimental Investigation on Ultrasonic Atomization Assisted Turning of Titanium Alloy - Jianbing Meng; Bingqi Huang; Xiaojuan Dong; Yizhong Hu; Yugang Zhao; Xiuting Wei; Xiaosheng Luan (Micromachines, 2020)
There are high cutting temperatures, large tool wear, and poor tool life in conventional machining, owing to the superior strength and low thermal conductivity of titanium alloy. In this work, ultrasonic atomization assisted turning (UAAT) of Ti6Al4V was performed with a mixed water-soluble oil-based cutting fluid, dispersed into tiny droplets by the high frequency vibration of a piezoelectric crystal. Different cutting speeds and two machining environments, dry and ultrasonic atomization assisted machining, were considered in the investigation of tool life, tool wear morphology, surface roughness, and chip morphology. In comparison with dry machining, UAAT shows lower tool wear and longer tool life due to the advantages of cooling and lubrication. Furthermore, better surface roughness, smoother chip edges, and shorter tool-chip contact length were obtained with UAAT.